Regulating Polygamy in Indonesia and Egypt Toward Greater Protection of Women (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2025)
This study examines the regulation of polygamy in Indonesia-Egypt and examines the extent to which these legal frameworks align with the protection of women within contemporary Islamic family law. The issue addressed arises from the persistent vulnerability of women in polygamous marriages, who are often exposed to economic insecurity, limited legal protection, psychological distress, and social marginalization. This study employs a normative legal research method using statutory, comparative, and conceptual approaches. Legal materials are analyzed through a qualitative normative analysis of marriage laws, judicial mechanisms, and Islamic legal doctrines governing polygamy in both countries. The findings indicate that the alignment of polygamy regulations toward women’s protection can be assessed through three main dimensions: economic protection, certainty of justice, and state recognition. Indonesia adopts a preventive–administrative model by requiring court permission, proof of economic capability, and the consent of the wife prior to polygamy. In contrast, Egypt applies a remedial judicial model by allowing polygamy with fewer preconditions while providing post-marital legal remedies, particularly the right of wives to seek divorce on the grounds of harm. However, both systems remain limited in delivering substantive protection for women, as legal safeguards tend to emphasize formal compliance rather than addressing psychological and social harms. This research implies the need for polygamy law reform that moves beyond procedural legality toward substantive gender justice grounded in maqāṣid al-sharī‘ah. The originality of this study lies in its integrated comparative analysis of normative, procedural, and protective dimensions of polygamy law in two Muslim-majority legal systems.